2017
DOI: 10.5812/jjm.13098
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Trends and The ESBL Prevalence of Escherichia coli and Klebsiella spp Urinary Isolates in In-and Outpatients in a Tertiary Care Hospital in Istanbul, 2004 - 2012

Abstract: Background: Extended spectrum beta-lactamase (ESBL) producing organisms causing urinary tract infections are increasing in incidence and becoming a serious health problem due to their resistance to large number of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
3
1
Order By: Relevance
“…[35][36][37] . In contrast, several studies reported the highest ESBL production among K. pneumoniae followed by E. coli which do not match our results [38][39][40] , since we found E. coli as the predominant ESBL producer.…”
Section: Percent Of Sensiɵvitycontrasting
confidence: 99%
“…[35][36][37] . In contrast, several studies reported the highest ESBL production among K. pneumoniae followed by E. coli which do not match our results [38][39][40] , since we found E. coli as the predominant ESBL producer.…”
Section: Percent Of Sensiɵvitycontrasting
confidence: 99%
“…The current results are in agreement with earlier study that only 35.6% of isolates were from men patients (Bakshi, et al, 2019). Other research has been shown that ESBL-producing E. coli incidences were significantly higher in females 73.6% than males 26.4% (Senbayrak, et al, 2017). It has been revealed that the high UTI prevalence in female can be attributed to many factors such as anatomical differing that allow quick admission of bacteria to the urinary tract (Rowe and Juthani-Mehta, 2013;Foad, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…According to an Iranian investigation, ESBL production was identified in 40.8% of all the isolates tested (Seyedjavadi, Goudarzi and Sabzehali, 2016), whereas other study reported 42.5% of the isolates recovered from outpatients (Koshesh, et al, 2016). Another investigation from tertiary care hospital in Istanbul revealed that 44.7% and 22.8% of isolates were ESBL enzyme producer among inpatients and outpatients, respectively (Senbayrak, et al, 2017). Based on the results of this study, the number of isolates that were found to be positive for AmpC screening were 27 (38.6%) which is in accordance to the previous published studies.…”
Section: Discussionmentioning
confidence: 97%
“…A study on examining the ESBL prevalence of E. coli isolated from urine samples of patients. The results of the study demonstrated that the prevalence of ESBL producers was a significant increase among isolates from inpatients (12.5 % to 44.7 %) and from outpatients (9.6 % to 22.8 %) (41). In 2012, 66 (37.1 %) of a total of 178 patients were ESBL positive-E. coli isolated from urine samples (n= 322) collected from Ankara Training and Research Hospital in Ankara province of Turkey (27).…”
Section: Discussionmentioning
confidence: 90%